Effects of postweaning supplementation of immunomodulatory feed ingredient on circulating cytokines and microbial populations in programmed fed beef heifers. (17th December 2021) - McCarty, Keelee J; Tipton, Jessie E; Ricks, Ralph E; Danielo, Jessica; Thompson, Jesse S; Block, Elliot; Pratt, Scott L; Long, Nathan M
Abstract: The objective was to determine the effects of an immunomodulatory feed ingredient following weaning on cytokine expression and fecal microbial populations of heifers. Commercial Angus heifers ( n = 72) were weaned (227 ± 7 d of age), blocked by BW ( n = 9 blocks), and randomly assigned to one of two pens per block. Pens within weight block (four heifers per pen) were then randomly assigned to treatments. Heifers were fed twice daily from days 0 to 60 (to gain 0.75 kg/d) and top dressed with either 18 g/heifer/d of the immunomodulatory feed ingredient (Celmanax; Arm and Hammer Animal Nutrition, Princeton, NJ; CEL ) or corn-germ meal (CON ). Blood samples were collected on days 0, 15, 30, 45, 60 and fecal grab samples on day 0 of the feeding trial. After day 60, two heifers per pen ( n = 32) were randomly selected for a transportation challenge. Serum samples were collected at hours 0, 4, 8, 12 and fecal grab samples at hours −24, 0, 24 and 7 d postchallenge. Blood samples were analyzed for interferonγ (IFNγ ), interleukin-8 (IL-8 ), and haptoglobin (HP ) using commercially available ELISA kits and qRT–PCR for genes of interest associated with cytokine expression. Fecal samples were enumerated for Clostridia and E. coli using selective media (≤5 isolates from each media/sample), tested to determine whether they were Clostridium perfringens or pathogenic E. coli, and then enriched for detection of Salmonella . Data were analyzed via ANOVA. During the feeding trial, HP was reduced ( P = 0.018) in CEL compared with CON at days 15, 45, and 60, whereas IFNγ and IL-8 did not differ ( P > 0.080) between treatments. All cytokines were decreased ( P < 0.001) in CEL compared with CON during the challenge. During the feeding trial, HP mRNA was increased ( P = 0.045) in CEL compared with CON at days 30 and 60. Similarly, IFNγ mRNA was increased ( P = 0.040) in CEL compared with CON; however, other genes of interest did not differ ( P > 0.172). Both C. perfringens and total E. coli counts were decreased ( P = 0.036) in CEL compared with CON at 24 h after the start of the transportation challenge. Clostridia and pathogenic E. coli counts did not differ ( P = 0.941) between treatments. Total Clostridia and E. coli counts were increased ( P < 0.014) 24 h postchallenge. All microbial populations, except pathogenic E. coli, observed decreased ( P ≤ 0.009) counts from 24 h to 7 d postchallenge. Overall, Celmanax supplementation decreased circulating cytokines, and altered microbial populations and gene expression, thus, may serve a role in preparing animals to better cope with immunological challenges. Lay Summary: With consumers wanting less antibiotic usage in cattle production, the need for natural feed ingredients that have positive effects on animal health are needed. The feeding of a yeast-based feed product decreased cytokines in the blood and their mRNA expression in white blood cells that act on stimulating an inflammatory response. When an animal has an inflammatory response, their immune system is working harder than necessary. This means they are using energy that could otherwise be used for growth, which decreases efficiency and performance. The feeding of this yeast-based feed ingredient also reduced the amount of harmful bacteria in the feces of the heifers. Having lower amounts of harmful bacteria (such as Salmonella ) in the feces decreases the chance of carcass contamination. For consumers, this means less instances of food-borne illnesses. Abstract : The feeding of a yeast-based feed products decreased cytokines in the blood and their mRNA expression in white blood cells that act on stimulating the inflammatory response. The feeding of this yeast-based feed ingredient also reduced the amount of harmful bacteria in the feces of the heifers.